CSR reporting in aviation : substantive actions or greenwashing? : case Lufthansa & Finnair - Mäkinen, Merlin (2021)
Corporate Social Responsibility (CSR) has gained importance and the expectations of stakeholders have increased. Better CSR reporting might give the company a competitive advantage over their peers and enhance corporate reputation. Motives behind CSR reporting could be answering to stakeholder claims, gaining legitimacy, or signalling about good behaviour. The objective of this thesis is to evaluate the current CSR reporting in aviation industry and to examine, what kind of aspects Lufthansa Group and Finnair highlight in their corporate responsibility reports and whether we can detect greenwashing. This is a comparative case study regarding Lufthansa Group’s and Finnair’s CSR reporting and the data is mainly collected from their sustainability and annual reports. The research method used was qualitative content analysis which focuses on the characteristics of language as communication. I also used summative approach to qualitative content analysis and counted and compared the keywords used in their reports. The theoretical part of this thesis will focus on CSR and CSR reporting according to Global Reporting Initiative (GRI) standards. I will also investigate previous research regarding greenwashing and focus on aviation industry specific research. The findings of the study were that emissions reduction was the dominant environmental theme. Regarding the social aspects highlighted, both airlines emphasised their goals to increase the share of women in management. The sustainability report of Lufthansa was more structured and comprehensive than Finnair’s and the data was easier to find. However, it seems that Finnair has made actions towards sustainability, but the problem arises with the communication of these actions and future goals. Some of the aspects can be viewed as greenwashing, such as withholding data to make valid comparisons, or highlighting aspects that do not offer viable solutions to the issues. However, the perception of greenwashing is subjective, and I can only point out some shortcomings regarding the reporting of these two airlines.